3D Printed Bioelectronic Platform with Embedded Electronics. (16th May 2018) - Agarwala, Shweta; Lee, Jia Min; Yeong, Wai Yee; Layani, Michael; Magdassi, Shlomo
Abstract: Silver nanoparticle based microelectrodes embedded between layers of hydrogel material were successfully fabricated. 3D bioprinting is employed to print the entire bioelectronics platform comprising of conducting silver ink and Gelatin methacryloyl (GelMA) hydrogel. The additive manufacturing technique of bioprinting gives design freedom for the circuit, saves material and shortens the time to fabricate the bioelectronics platform. The silver platform shows excellent electrical conductivity, structural flexibility and stability in wet environment. It is tested for biocompatibility using C2C12 murine myoblasts cell line. The work demonstrates the potential of the fabricated platform for the realization of practical bioelectronic devices.